META-ANALYSIS: THE GUIDED INQUIRY LEARNING MODELS EFFECT ON STUDENTS LEARNING OUTCOMES IN CHEMICAL LEARNING - Rindiany, Nindy Aprillia; Aini, Faizah Qurrata (FKIP USK, 2024)
The guided inquiry learning model is an appropriate pedagogical approach for teaching chemistry, as it engages students directly in the learning process. The objective of this research was to analyze and determine the effect of the guided inquiry learning model on students' learning outcomes in chemistry. This research is a literature study that employs a meta-analysis approach, adapted from the PRISMA methodology. A total of 200 articles published on Google Scholar between 2020 and 2024 were collected using the Publish or Perish application with the keywords